Une tradition disputée : enjeux identitaires dans une communauté des Andes boliviennes - Vanina Bouté (Journal de la Société des Américanistes)
The keenly contested tradition: identity issues in a comunity of the bolivian Andes. This paper aims at analysing conflicts between various social groups within a community of the Bolivian Altiplano ; those conflicts can primarily be traced back to the decay of traditional power bonds that existed before the Agrarian Reform of 1953. Underlying these conflicts is a representation of the past, to be perpetuated, reinvented or rejected. We will thus see how these various representations, creating tensions and renegociations between groups, are mainly expressed through differentiated religious celebrations.